The Effectiveness of using Student Worksheets to Practice Science Process Skills on Hooke's Law Material - S Syamsidar; Khaeruddin Khaeruddin; Helmi Helmi (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2021)
This study aims to analyze the effectiveness of guided inquiry-based physics worksheets in training students' science process skills. This case study was conducted at SMAN 4 Sidenreng Rappang with 28 respondents. Students use worksheets based on guided inquiry for four meetings in Hooke's law material. The worksheets were developed using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation, including expert validation. We obtained the expert analysis of student worksheets based on guided inquiry from two experts, namely 3.16 out of 4 Likert scales with a validity percentage of 78.89%. These results indicate that the student worksheets based on guided inquiry are appropriate. Also, the gain test is used to determine the effectiveness of this worksheet. The science process skills test score obtained an average N-gain of 0.69, and this value is included in the medium category. This is shown based on student responses which found that 28 respondents generally gave a positive reaction to guided inquiry-based physics worksheets. This means that students receive guided inquiry-based physics worksheets as an effective learning resource used in learning.